Liberation theology and sexuality - Althaus-Reid, Marcella (SCM Press, 2009)
'Let them talk ...!' Doing liberation theology from Latin American closets /Marcella Althaus-Reid --Once again liberating theology? Towards a Latin American liberation theological self-criticism /Otto Maduro --Queer eye for the straight guy: the making over of liberation theology, a queer discursive approach /Ivan Petrella --Oh, que sera, que sera ... A limping a/theological thought in Brazil /Claudio Carvalhaes --Commodity aesthetics and the erotics of relationship: challenges of feminist hermeneutics of liberation to market aesthetics /Nancy Cardoso Pereira --The prostitutes also go into the kingdom of God: a queer reading of Mary of Magdala --Martin Hugo Cordova Quero --Liberation theology, modernity and sexual difference /Mario Ribas --Liberating Mary, liberating the poor /Frederico Pieper Pires --Seriously harmful for your health? Religion, feminism and sexuality in Latin America /Elina Vuola --Worship and the excluded /Jaci Maraschin --Love in times of dictatorships: memoirs from a gay minister from Buenos Aires /Roberto Gonzalez with Norberto D'Amico.